2019
DOI: 10.1016/j.omtm.2019.10.012
|View full text |Cite
|
Sign up to set email alerts
|

A Sendai Virus-Based Cytoplasmic RNA Vector as a Novel Platform for Long-Term Expression of MicroRNAs

Abstract: Cytoplasmic RNA virus-derived vectors have emerged as attractive vehicles for microRNA (miRNA) delivery as they possess no potential risk of chromosomal insertion. However, their relatively short-term expression limits their use in biological applications that require long-term miRNA manipulation, such as somatic cell reprogramming. Here, we show that a cytoplasmic RNA virus vector based on a replication-defective and persistent Sendai virus (SeVdp) serves as an effective platform for long-term production of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…These results suggested that insertion of the AGIA epitope between UbC11 and POI avoided steric hindrance of the POI and allowed endogenous DUBs to more easily access UbC11, resulting in improved cleavage efficiency. Next, we tested this system using Sendai virus (SeV) vectors, 36,37 which are cytoplasmic RNA virus-derived vectors that have no risk of chromosomal insertion and strong gene expression capability. Because RNA virus-based vectors, such as the SeV vector, are not compatible with conditional and inducible promoter systems, such as the tetracycline (Tet)-On/Off system, we assumed that our c-DUB system would achieve the conditional control of a protein target under SeV vectors.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These results suggested that insertion of the AGIA epitope between UbC11 and POI avoided steric hindrance of the POI and allowed endogenous DUBs to more easily access UbC11, resulting in improved cleavage efficiency. Next, we tested this system using Sendai virus (SeV) vectors, 36,37 which are cytoplasmic RNA virus-derived vectors that have no risk of chromosomal insertion and strong gene expression capability. Because RNA virus-based vectors, such as the SeV vector, are not compatible with conditional and inducible promoter systems, such as the tetracycline (Tet)-On/Off system, we assumed that our c-DUB system would achieve the conditional control of a protein target under SeV vectors.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the context of polycistronic miRNA clusters, the miR-367 processing was most efficient, which has been demonstrated previously for Sendai virus vector-based delivery. 13 Therefore, one of the critical issues for the future development of the taRNA-based system is the identification of more efficient miRNA backbones for taRNA-miR. Another issue relates to the improvement of the efficacy of the mRNA processing by the engineering of pre-miRNA hairpin cleavage sites, which can have a positive effect on pre-miRNA processing by Drosha.…”
Section: Main Textmentioning
confidence: 99%
“…It is also well-known for its high transduction efficiency compared to other methods [ 63 ]. Another recent study showed the ability of SeV vector to produce small regulatory RNAs with high transduction efficiency, durable expression, low cytotoxicity, and less risk of chromosomal insertion [ 32 ]. Although the SeV vector is known as being “ex-gene-free”, several researchers are still unsure of its safety in producing clinical-grade iPSC lines, as the avoidance of transgene integration passively depends on the cell passage [ 64 ].…”
Section: Non-integrating Lentiviral Vector (Nilv) Designmentioning
confidence: 99%